Effects of flushing, altrenogest, and pubertal status on litter traits in gilts - Rhodes, M.T.; Davis, Duane L.; Stevenson, Jeffrey S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
We tested the effects of flushing (3.4 lb extra ground sorghum grain for at least 10 days before estrus) and estrous synchronization with altrenogest on litter traits in gilts. Altrenogest had no effect on litter size or weight, but flushing increased both traits. The response to flushing occurred entirely among gilts artificially inseminated at the pubertal estrus. Pubertal gilts represented approximately 40% of the gilts in our experiment, and their improvement in litter size was almost two pigs. When all gilts were considered, flushing improved litter size by .9 pigs.
Keywords: Swine; Flushing; Altrenogest